Antifungal susceptibility testing of few medicinal plant extracts against Aspergillus spp. and Microsporum sp. - Manoharan Sharanya, Iyappan Ramalakshmi Oviya, Vasudevan Poornima and Muthusamy Jeyam (Journal of Applied Pharmaceutical Science, 2013)
Mycoses are fungal infections, the incidence of which in immunocompromised patients is currently devastating and the drugs available at hand are reported to exhibit side effects. To surmount the prevailing difficulty of complete eradication of the fungal infection, exploring new arena is a requisite and nature’s wealth can be one area that may lead to a cure for fungal infections. In the present study, the whole methanolic extracts of few medicinal plants were evaluated against Aspergillus flavus, Aspergillus fumigatus, Aspergillus niger and the dermatophyte Microsporum gypseum isolated from the soil. Enicostemma littorale and Wrightia tinctoria exhibited significant (P
Keywords: Antifungal assay, keratin-baiting technique,